Detección del virus de la Hepatitis B mediante técnicas inmunológicas y moleculares - Josselin Marina, Velín Torres (2021)
ABSTRACT The hepatitis B virus (HBV) infection can cause acute or chronic hepatitis with long-term complications. Well-defined and verified diagnostic markers allow assessment of disease severity, viral replication status, patient risk stratification, and treatment decisions. The purpose of this study was to describe the importance and scope of immunological and molecular techniques in the detection of HBV for the diagnosis of acute and chronic infection, focused on the interaction between virus replication and host immunity. The research was based on a meticulous search process of scientific documents published in digital databases: PubMed, Scopus, Elsevier, Science Direct, Google Scholar, Medline, Springer, Scielo, Web of Science, and Redalyc ProQuest and Britannica Academic; As well as epidemiological data reported by the official world and national organizations. Of 56 articles read in detail, 12 were selected for their description in the development considering the inclusion criteria. Determination of serological markers (HBV antigens and antibodies against them) and DNA detection by molecular methods are used in the differential diagnosis of HBV infection, monitoring the course of infection in patients, screening for blood products looking for infectivity, the evaluation of immunity and the effectiveness of antiviral therapy in patients with chronic hepatitis B. Key words: hepatitis B, diagnosis, immunological tests, antigens, antibodies, molecular tests, infection, chronic infection.